Intergenerational Collaboration and Social Adaptation in the Digital Workplace Era - Murni, Maria Goreti; Wuri, Ignatius; Leto, Ama (Journal Social Humanity Perspective, 2023)
In this qualitative study, the author will explore the implications of changes in technology on social dynamics through an analysis of collaborative practices of the Millennial and Baby Boomer generation under the digital generation. In the environment of constant digitalization, modern organizations are starting to seek the services of multigenerational teams where members demonstrate different degrees of digital fluency, styles of communication, and values at work. Based on the results of extensive interviews with workers of various industries, this paper shows that technology is a mediator and a booster of intergenerational differences. The findings reveal that a majority of Millennials quickly learn how to use new and emerging digital technologies, although Baby Boomers tend to provide vital experiences of a lifetime and the foresight. However, existing collaboration is still affected by breaches of communication, a mismatch of expectations on the freedom of action, and power and competence issues in technological innovation. Four key dynamics are found in analysis, namely divergent perceptions of technological change, communication issues linked to digital fluency, adaptive learning strategies deployed both between and within generations, and negotiation of trust, respect, and role in teams. The above dynamics are not just behavioral ones, as they are engraved in generational identities based on historical context and organizational culture. The research finds that appropriate handling of intergenerational teams in the digital age needs to be approached as more than technical training, but rather through deliberate plans that promote trust in each other, inclusive learning experiences as well as the flexible redefinition of roles.